Analysis Of The Effect Of Financial Leverage On Financial Performance Of Listed Property & Real Estate Sector Companies On The Indonesian Stock Exchange Period 2019 – 2023 - Ahmad Faisal; Syahyunan Syahyunan; Teguh Setiawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the Effect of Financial Leverage on Financial Performance in Property & Real Estate Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period. In this study, the author examines the effect of Financial Leverage represented by its independent variables, namely, Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Interest Coverage Ratio (ICR) on Financial Performance with indicators represented by Return On Assets (ROA) as the dependent variable using a quantitative approach. The data taken in the study are financial report data found on the official website of the Indonesia Stock Exchange. The sampling technique used is purposive sampling and obtained 10 companies according to the research sample requirements with a research period of 5 consecutive years, thus obtaining 50 data samples. The data analysis method in this study is panel data regression analysis using Eviews 12.0 software. The results of the study indicate that simultaneously the relationship between independent variables, namely, Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), and Interest Coverage Ratio (ICR) on the dependent variable, namely, Financial Performance (Return On Asset = ROA) is able to have a significant influence. While partially, the relationship between Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) has a negative and significant influence on Financial Performance (Return On Asset = ROA). However, the relationship between Interest Coverage Ratio (ICR) on Financial Performance (Return On Asset = ROA) does not have a significant influence.